2017
DOI: 10.1002/jbt.21974
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant protection by β‐selenoamines against thioacetamide‐induced oxidative stress and hepatotoxicity in mice

Abstract: Thioacetamide (TAA) is a hepatotoxin that rapidly triggers the necrotic process and oxidative stress in the liver. Nevertheless, organic selenium compounds, such as β-selenoamines, can be used as pharmacological agents to diminish the oxidative damage. Thus, the aim of this study was to investigate the protective effect of the antioxidant β-selenoamines on TAA-induced oxidative stress in mice. Here, we observed that a single intraperitoneal injection of TAA (200 mg/kg) dramatically elevated some parameters of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In the present investigation, TAA was used to induce hepatotoxicity in the rat experimental model. [26,27] It has been reported that TAA successfully induces an experimental rat model of hepatic fibrosis when dosed with 200 mg/kg, intraperitoneally (IP) twice a week for 6 consecutive weeks. [28,29] We have used DMF as an intervention agent, and the dose was selected considering that at least two doses should fall in the dose range used in clinics.…”
Section: The Rationality Of Dose Selectionmentioning
confidence: 99%
“…In the present investigation, TAA was used to induce hepatotoxicity in the rat experimental model. [26,27] It has been reported that TAA successfully induces an experimental rat model of hepatic fibrosis when dosed with 200 mg/kg, intraperitoneally (IP) twice a week for 6 consecutive weeks. [28,29] We have used DMF as an intervention agent, and the dose was selected considering that at least two doses should fall in the dose range used in clinics.…”
Section: The Rationality Of Dose Selectionmentioning
confidence: 99%
“…14,23 TASO and TASO 2 are ultimate hepatotoxicants and cause centrilobular necrosis of hepatocytes by covalent binding to proteins and lipids 19,23,33,60 and/or induction of oxidative stress such as lipid peroxidation. 30,55,56,57 Oxidative stress such as generation of hydroxyl radicals and other electrophilic molecules can cause DNA damage including double-strand breaks. 16,38 In the TAA model, dietary iron overload enhances TAA-induced hepatocellular injury with increased DNA damage and hepatic MDA content.…”
Section: Resultsmentioning
confidence: 99%
“…Acute hepatic and kidney injury was induced by a single 200 mg/kg TAA intraperitoneal injection as previously described [ 29 ]. Mice (n = 30) were randomly divided into five sets (6 mice/group): The control (CTRL) group, where mice received normal saline; the OA group that was treated with OA (90 mg/kg/day for 7 days); the TAA group, where mice were injected with TAA; the OA 45 + TAA and OA 90 + TAA groups, where mice received OA at 45 and 90 mg/kg, respectively, for 7 days before TAA challenge.…”
Section: Methodsmentioning
confidence: 99%